Consumer attitude towards value added products of Kerala State Cashew Development Corporation - Aravind P L (College of Co-operation, Banking and Management, 2017)
In this context the present study entitled “Consumer Attitude Towards Value Added Products of Kerala State Cashew Development Corporation” has done with the objectives: To know the consumer’s attitude and retailers’ perception towards value added products of KSCDC. The study was conducted in four different locations of Kollam district during the months of August and September 2017. For the analysis of above objectives, primary data were collected through structured questionnaires for retailers and consumers of the product from selected research area.